Midwifery and Medicine in Boston Walter Channing, M.D., 1786-1876 - Kass, Amalie M. (Northeastern University Press, 2019)
This first biography of the prominent obstetrician vividly depicts the life and career of a multi-faceted man and offers fresh perspectives on medicine, society, and women's reproductive lives in nineteenth-century America. Originally published by Northeastern University Press in 2002. With a new foreword by Scott Podolsky, M.D.